Implementasi Qanun No. 11/2018 di Aceh Barat: Literasi Masyarakat, Praktik Lembaga, dan Peran Dewan Pengawas Syariah - Mulia Safitri; Muflihatul Fauza; Lia Mursila (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study examines the implementation of Aceh Qanun No. 11/2018 on Sharia Financial Institutions (LKS) in West Aceh, focusing on public literacy and user experience, institutional constraints, and the role of Sharia Supervisory Boards (DPS). Employing a qualitative case-study approach, data were gathered through interviews, limited observation, and document analysis at Bank Syariah Indonesia (BSI) Meulaboh, Bank Aceh Syariah Meulaboh, and a sharia cooperative/BMT in Meureubo, involving 15 purposively selected informants. Guided by institutional theory and diffusion of innovations, the analysis shows that strong regulatory pressure accelerates formal compliance, while public understanding remains largely declarative. Users experience moral reassurance alongside complex procedures, confusing contract terminology, and unequal urban-rural access. Banks adapt more effectively than cooperatives/BMT, which face sharper resource constraints. Although DPS exists formally, its oversight is perceived as episodic and document-oriented, enabling partial decoupling. Sustaining the Qanun requires strengthening public literacy, frontline competence, and proactive DPS engagement to move from symbolic to informed compliance.